Emergence of MXene-based electrochemical biosensors for biomolecule and pathogen detection - Aibobek Seitak; Shaohong Luo; Ning Cai; Kin Liao; Anna-Maria Pappa; Sungmun Lee; Vincent Chan (Sensors and Actuators Reports, 2023)
MXenes, is an attractive new class of two-dimensional (2D) materials, discovered in 2011. Since then, owing to their unique combination of properties, such as high specific area, high electrical conductivity, tunable hydrophilicity, tunable chemical composition, and potential cytocompatibility, MXenes have made a deep impact on various fields ranging from electronics to energy and more recently to biotechnology. A typical example for the latter, is their use as electroactive biointerfaces in a number of biosensor setups, exhibiting remarkable analytical performance. In particular, MXene-based nanocomposites can serve as bioreceptors, electrochemical transducers or amplification probes towards translating molecular recognition of biological targets into detectable signals, leading to ultrasensitive biosensors for probing biomarkers, or pathogens. This concise review highlights the recent advances of MXene-based electrochemical biosensors for highly selective and sensitive detection of nucleic acids, proteins and pathogens pertaining to biomarker identification and clinical diagnostics. In particular, the effects of synthetic routes, surface chemistry, nanocomposite design, and fabrication methods of MXenes on the resulting relationship between biointerfacial structure, electrochemical properties and device performance is discussed, providing unique perspectives and design criteria for the next wave of biosensors.